2021
DOI: 10.3390/jcm10132864
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Ability of Peguero-Lo Presti Electrocardiographic Left Ventricular Hypertrophy Criterion in Severe Aortic Stenosis

Abstract: Traditional electrocardiographic (ECG) criteria for left ventricular hypertrophy (LVH), introduced in the pre-echocardiographic era of diagnosis, have a relatively low sensitivity (usually not exceeding 25–40%) in detecting LVH. A novel Peguero-Lo Presti ECG-LVH criterion was recently shown to exhibit a higher sensitivity than the traditional ECG-LVH criteria in hypertension. Our aim was to test the diagnostic ability of the novel Peguero-Lo Presti ECG-LVH criterion in severe aortic stenosis. We retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The ROC curve showed that the Peguero-Lo Presti index had an AUC of 0.80, indicating its good overall performance compared to Skolow-Lyon (0.73) and Cornell (0.66). The results of this study are consistent with those of Gamrat et al which showed that the Peguero-Lo Presti index had improved sensitivity and specificity compared to the Sokolow-Lyon and Cornell-Voltage sensitivity (55% versus 9% at 34%) and specificity (78% versus 71% at 70%) in the diagnosis of LVH [21]. When screening for LVH in patients with cardiovascular disease, routine use of the Peguero-Lo Presti index should be considered [22] concluded by these authors.…”
Section: Discussionsupporting
confidence: 91%
“…The ROC curve showed that the Peguero-Lo Presti index had an AUC of 0.80, indicating its good overall performance compared to Skolow-Lyon (0.73) and Cornell (0.66). The results of this study are consistent with those of Gamrat et al which showed that the Peguero-Lo Presti index had improved sensitivity and specificity compared to the Sokolow-Lyon and Cornell-Voltage sensitivity (55% versus 9% at 34%) and specificity (78% versus 71% at 70%) in the diagnosis of LVH [21]. When screening for LVH in patients with cardiovascular disease, routine use of the Peguero-Lo Presti index should be considered [22] concluded by these authors.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the overall diagnostic accuracy of the Peguero-Lo Presti criterion is reliable for HCM. Recently, Gamrat et al [26] applied the Peguero-Lo Presti criterion to detect LVH in patients with severe aortic stenosis. The results showed that the Peguero-Lo Presti criterion had improved sensitivity (55% vs. 9%-34%) and decreased specificity (72% vs. 78%-100%) for the detection of LVH compared with 8 single traditional ECG criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the Peguero-Lo Presti criterion had improved sensitivity (55% vs. 9%–34%) and decreased specificity (72% vs. 78%–100%) for the detection of LVH compared with 8 single traditional ECG criteria. Compared with the traditional ECG-LVH criteria, the agreement between Peguero-Lo Presti criterion and echocardiographic LVH in patients with severe aortic stenosis was slightly better [ 26 ]. Matusik et al .…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for left ventricular hypertrophy were as follows: a left ventricular mass index > 125 g/m 2 for men and >120 g/m 2 for women. 12 Left ventricular systolic dysfunction was defined as an ejection fraction (EF) <50.0%, 13 and a left ventricular diastolic dysfunction as an E/A <1.0. 14 In addition, the number of hospitalizations of the individuals in the two groups in one year were counted, and the distribution of causes (bleeding, infection and embolism) was analyzed.…”
Section: Avf-groupmentioning
confidence: 99%